The sociology of Islam : knowledge, power and civility - Salvatore, Armando (Hoboken, N.J. : Wiley, 2016)
'The Sociology of Islam is an interpretive account of Islam as a religion and civilization in world history and global society, which focuses on the notions of knowledge-culture, power and civility to provide key interpretive and analytic tools to practitioners. The first substantial introduction to the field of the Sociology of Islam that combines theoretical reflections with historical analysis Explores the original civilizational trajectory of Islam and its specific entry point into modernity Develops a narrative and analytic thread that makes the'dual' role of Islam - as a religion and civilization - comprehensible to non-specialists Allows Islamic Studies specialists and students to locate the study of Islam in a comparative perspective with the help of simple, yet rigorous conceptual tools drawn from sociology and social theory The author is a scholar of both the Sociology of Islam and Comparative Civilizational Analysis and ideally placed to write this text'--
'The Sociology of Islam provides an accessible introduction to this emerging field of inquiry, teaching and debate. The study is located at the crucial intersection between a variety of disciplines in the social sciences and the humanities. It discusses the long-term dynamics of Islam as both a religion and as a social, political and cultural force. The volume focuses on ideas of knowledge, power and civility to provide students and readers with analytic and critical thinking frameworks for understanding the complex social facets of Islamic traditions and institutions. The study of the sociology of Islam improves the understanding of Islam as a diverse force that drives a variety of social and political arrangements. Delving into both conceptual questions and historical interpretations, The Sociology of Islam is a transdisciplinary, comparative resource for students, scholars, and policy makers seeking to understand Islam's complex changes throughout history and its impact on the modern world'--
The Institutional Mold of Islamic Civility: Contractualism vs. Corporatism?From the Postcolonial Condition toward New Fragile Patterns of Translocal Civility; References; Index; EULA
Machine generated contents note: Preface and Acknowledgments Introduction Knowledge and power in the sociology of Islam Knowledge/charisma vs. power/wealth: the challenge of religious movements Civility as the engine of the knowledge-power equation: Islam and'Islamdom' Part I. Patterns of Civility 1. The Limits of'Civil Society' and the Path to Civility The origins of modern civil society Civil society as a site of production of modern power Folding civil society into a transversal notion of civility 2. Brotherhood as a Matrix of Civility: The Islamic Ecumene and Beyond Between networking,'charisma' and social autonomy: the contours of'spiritual' brotherhoods Beyond Sufism: the unfolding of the brotherhood Rewriting charisma into brotherhood Part II. Islamic Civility in Historical and Comparative Perspective 3. Flexible Institutionalization and the Expansive Civility of the Islamic Ecumene The steady expansion of Islamic patterns of translocal civility Authority, autonomy, and power networks: A grid of flexible institutions The permutable combinations of normativity and civility 4. Social Autonomy and Civic Connectedness: The Islamic Ecumene in Comparative Perspective New patterns of civic connectedness centered on the'commoners' Liminality, charisma and social organization Municipal autonomy vs. translocal connectedness Part III. Modern Islamic Articulations of Civility 5. Knowledge and Power: The Civilizing Process before Colonialism From the Mongol impact to the early modern knowledge-power configurations Taming the warriors into games of civility? Violence, warfare and peace The long wave of power decentralization 6. The Implosion of Traditional Institutions and Norms under the Impact of Colonial Blueprints of Order and Civility The metamorphosis of civility under colonialism Court dynamics and emerging elites: the complexification of the civilizing process Class, gender and generation: The ultimate testing grounds of the educational-civilizing project 7. Global Civility and its Islamic Articulations The dystopian globalization of civility Diversifying civility as the outcome of civilizing processes From Islamic exceptionalism to an Islamic perspective Conclusion Overcoming Eurocentric views: religion and civility within Islam/Islamdom The institutional mold of Islamic civility: contractualism vs. corporatism? From the postcolonial condition towards new fragile patterns of translocal civility Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Islamic sociology; Civil society -- Islamic countries; Electronic books